Development of Tire Pressure Monitoring System Using Vibration Energy Focusing on Electromagnetic Energy Harvester - Hazamudin, Muhammad Hadiratul Quddus (Universiti Teknologi PETRONAS, 2021)
Tire Pressure Monitoring System (TPMS) is a module that provides real-time information regarding the air pressure inside the tire to the driver and also will give a warning signal to the driver if the air pressure inside the tires falls below the recommended tire air pressure value. TPMS usually consists of wireless sensors also known as the transmitter which are installed in each tire of a vehicle and the receiver that is the user interface that is placed inside the vehicle for the driver to view. Furthermore, an average TPMS module utilizes a battery to power the module, however, the drawback of using the battery is the limited life span of the battery and the high cost for the battery replacement. On the other hand, energy harvesting is a process where electrical energy is generated from external ambient energy. The electromagnetic energy harvesting method is considered to be the most suitable for powering the TPMS module because the electromagnetic energy harvester has a good energy density, high reliability and can withstand the harsh surrounding that occurs inside the tire which includes the high temperature and high-pressure environment.